The students attitudes' toward the flipped classroom strategy and relationship to self-learning skills - Hussain Aburayash (Intelektual Pustaka Media Utama, 2021)
The study aimed to identify the attitudes of students of open education towards the flipped class strategy of the opposite grade and its relation to self-learning skills. To achieve the goals of the study, the measure of the direction towards education was constructed in the opposite grade and the self-learning skills scale. The sample of the study consisted of 60 male and female students of higher diploma in education studying the decisions of the educational administration and Educational Psychology in the Arab Open University/Jordan. The results of the study showed a positive trend for university students towards education in the opposite grade, with the percentage of the trends as a whole 90%. The results also showed a positive correlation between each of the students' attitudes toward education in the opposite grade and each of the variables (academic motivation, self-monitoring, self-learning skills, self-learning writing skills), and no correlation between students' and skills in dealing with information technology.